2016
DOI: 10.1007/s11629-015-3813-2
|View full text |Cite
|
Sign up to set email alerts
|

Estimating cropland carbon mitigation potentials in China affected by three improved cropland practices

Abstract: Abstract:emissions. substitution are benefic stocks and addition to and fossil practices

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Studies have shown that returning straw to the field is beneficial to the improvement of soil properties, thereby increasing crop yields. [109,110]. The rapid degradation of straw is particularly important.…”
Section: Potential Application In Soil Quality Improvementmentioning
confidence: 99%
“…Studies have shown that returning straw to the field is beneficial to the improvement of soil properties, thereby increasing crop yields. [109,110]. The rapid degradation of straw is particularly important.…”
Section: Potential Application In Soil Quality Improvementmentioning
confidence: 99%
“…Although previous research has made valuable efforts, there is still great uncertainty in accurately quantifying harvested carbon in cropland (HCC) ecosystems (Smith et al 2010, Lun et al 2016. For example, the CLM5.0 crop model can reproduce the observed long-term trend of crop yields with relative accuracy before 1990 but showed a substantial underestimation after 1990 (Lombardozzi et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Direct consequence of this negative impact is the fact that since the beginning of the 3rd millennium the world agriculture has left behind industry and transportation, burning fossil fuels, mainly due to plowing of a large array of lands (Сsoil+ О 2 atmosphere = СО 2 ) by emissions of carbon monoxide to atmosphere by 10% (Lun et al, 2016;.…”
mentioning
confidence: 99%